The aspects of classification and examination of cigarettes in the course of forensic commodity examination - N. V. Kryvoruchko; T. S. Kyrychenko (Bulletin of Kharkiv National University of Internal Affairs)
The article deals with the methodological and practical aspects of conducting a forensic commodity examination of cigarettes, which are a specific segment of the consumer market. The main attention is paid to the issues of classification of tobacco products, determination of their quality and compliance with the established standards. The examination takes into account key product characteristics, such as physical and chemical composition, consumer properties, packaging and labelling features, as well as compliance with the declared characteristics. The article analyses modern methods of cigarette examination, including physical and chemical analysis of tobacco mixtures, aerosol testing, inspection of filter and cigarette paper properties, and assessment of labelling compliance with standards. Particular attention is paid to identifying defects in cigarettes that may arise as a result of process, storage or transportation violations. Such defects include uneven filling of the tobacco mixture, damage to the packaging, foreign impurities, leaks and poor quality of filter materials. The article describes the sequence of actions that are carried out during the examination, starting with visual inspection of the sample, study of physical characteristics, laboratory analysis and ending with comparison of the results with established standards, such as national and international regulations. The importance of an integrated approach to the examination is emphasised, which allows to assess the quality of products, identify possible violations and protect consumer rights. Determining the compliance of cigarettes with regulatory requirements helps to detect counterfeits, comply with product safety requirements for consumers and improve the quality of products on the market. The results of the study can be used to improve the methods of forensic commodity examination, increase the level of quality control over tobacco products and help ensure their compliance with international standards.